Full-cement-based supercapacitor and preparation method thereof

By using porous foamed cement as an isolation device in cement-based supercapacitors, the problem of physical performance degradation caused by the increase in the amount of conductive carbon black is solved, and the efficiency, durability and applicability of all cement supercapacitors are achieved.

CN119852100APending Publication Date: 2025-04-18SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510011130.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When existing cement-based supercapacitors increase the amount of conductive carbon black to increase capacitance, their physical properties will be greatly reduced, limiting their application prospects in actual engineering.

Method used

Porous foamed cement is used as the isolation device for the positive and negative electrodes of the carbon-cement electrode supercapacitor to build a fully cemented supercapacitor with cement-based electrode + cement-based separator.

Benefits of technology

It realizes the low cost, high structural stability, excellent physical performance, high assembly efficiency and good durability of all cement supercapacitors, and is suitable for practical engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852100A_ABST
    Figure CN119852100A_ABST
Patent Text Reader

Abstract

The invention provides a full-cement-based supercapacitor and a preparation method thereof, and relates to the technical field of supercapacitors. The full-cement-based super capacitor comprises a first cement-based electrode, a second cement-based electrode, and a foaming cement isolation layer between the first cement-based electrode and the second cement-based electrode. The invention constructs a full-cement type super capacitor with a cement-based electrode and a cement-based diaphragm, and the capacitor is low in cost, has relatively high structural stability, excellent physical performance, high assembly efficiency and good durability, and is expected to be applied to actual engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cement-based supercapacitors, and in particular to a full-cement-based supercapacitor and a preparation method thereof. Background Art

[0002] At present, cement-based supercapacitors are basically supercapacitors with cement-based materials as electrolytes. Only a paper published last year (Carbon-cement supercapacitors as a scalable bulk energy storage solution) proposed a new solution to store electrical energy in cement - a supercapacitor based on cheap and easily available cement, water and carbon black with carbon-cement as electrodes. However, this supercapacitor has the following problems: the increase in the amount of active material, namely conductive carbon black, can effectively increase the capacitance, but the physical properties will be greatly reduced, which seriously hinders the application prospects of this supercapacitor in actual engineering. Summary of the invention

[0003] The present invention constructs a full-cement supercapacitor of cement-based electrode + cement-based diaphragm by using porous foamed cement as the isolation device for the positive and negative electrodes of the carbon-cement electrode supercapacitor. The capacitor has low cost, high structural stability, excellent physical properties, high assembly efficiency, good durability, and is expected to be applied to practical engineering.

[0004] One of the purposes of the present invention is to provide a full cement-based supercapacitor.

[0005] The second object of the present invention is to provide a method for preparing the all-cement-based supercapacitor.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] In a first aspect, the present invention provides a fully cement-based supercapacitor, comprising a first cement-based electrode, a second cement-based electrode, and a foamed cement isolation layer between the first cement-based electrode and the second cement-based electrode;

[0008] The foamed cement isolation layer is prepared by the following method:

[0009] Cement and water are mixed and stirred evenly to form cement slurry; H2O2 with a concentration of 2% to 4% is added to the cement slurry, poured into a mold, and demolded and cured after forming to obtain a foamed cement isolation layer.

[0010] Preferably, the cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement. The cement strength grade may be 425, 625, 325, 525, etc., without particular limitation;

[0011] Preferably, the water-cement ratio is 0.3-0.6.

[0012] Preferably, the curing temperature is 20±2° C., the relative humidity is controlled at above 95%, and the curing period is more than 28 days.

[0013] Preferably, the thickness of the foamed cement isolation layer is 1-10 mm.

[0014] The pores of the prepared foamed cement isolation layer are 0.5-5 μm.

[0015] In some embodiments, the first cement-based electrode and the second cement-based electrode are each independently prepared by the following method:

[0016] Conductive carbon black and cement are mixed to obtain a dry mixture, water and a water reducing agent are added and mixed to obtain a cement-based slurry; the cement-based slurry is poured into a mold and vibrated, and after hardening, it is demolded, cured, cut, and polished to obtain a cement-based electrode.

[0017] Preferably, the conductive carbon black is one or more selected from acetylene black, SP, and Ketjen black, and the specific surface area of ​​the conductive carbon black is 50 m 2 / g-1200m 2 / g;

[0018] Preferably, the cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement. The cement strength grade may be 425, 625, 325, 525, etc., without particular limitation;

[0019] Preferably, the mass of the conductive carbon black accounts for 8% to 13% of the mass of the cement;

[0020] Preferably, the water reducer is one or more selected from polycarboxylic acid high-efficiency water reducer, naphthalene-based high-efficiency water reducer, and aminosulfonate-based high-efficiency water reducer, preferably polycarboxylic acid high-efficiency water reducer.

[0021] Preferably, the water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 2% to 4% of the mass of water.

[0022] Preferably, the curing temperature is 20±2° C., the relative humidity is controlled at above 95%, and the curing period is more than 28 days.

[0023] Preferably, the thickness of the first cement-based electrode and the second cement-based electrode are each independently 1-30 mm.

[0024] Before being assembled into a supercapacitor, the first cement-based electrode and the second cement-based electrode are immersed in an electrolyte (such as 1M potassium chloride solution) until saturated.

[0025] In some embodiments, the all-cement-based supercapacitor also includes: a first foamed cement bearing layer and a second foamed cement bearing layer, the first foamed cement bearing layer is arranged on the side of the first cement-based electrode away from the foamed cement isolation layer, and the second foamed cement bearing layer is arranged on the side of the second cement-based electrode away from the foamed cement isolation layer; wherein the first foamed cement bearing layer and the second foamed cement bearing layer are each independently prepared by the following method: mixing cement, water and fine aggregate, stirring evenly to form a cement slurry; adding H2O2 with a concentration of 6% to 10% to the cement slurry, pouring it into a mold, demolding and curing after molding, to obtain a foamed cement bearing layer.

[0026] Preferably, the cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement. The cement strength grade may be 425, 625, 325, 525, etc., without particular limitation;

[0027] Preferably, the mass of fine aggregate is 2-2.5 times the mass of cement; and the water-cement ratio is 0.3-0.6.

[0028] Preferably, the curing temperature is 20±2° C., the relative humidity is controlled at above 95%, and the curing period is more than 28 days.

[0029] Preferably, the thickness of the first foamed cement bearing layer and the second foamed cement bearing layer are independently 10-50 mm.

[0030] The pores of the prepared foamed cement bearing layer are 0.2-1 mm.

[0031] The porous cement bearing layer can help evenly distribute the mechanical loads applied inside and outside the capacitor, reduce local stress concentration, and avoid material failure caused by excessive local loads. It provides sufficient rigidity and strength for the mechanical support of the supercapacitor. The porous cement structure has good energy absorption characteristics, which can absorb and buffer external impact forces and prevent the capacitor from being damaged when subjected to external impacts.

[0032] In some embodiments, the all-cement-based supercapacitor also includes: a first polymer gel layer and a second polymer gel layer, the first polymer gel layer is arranged between the first cement-based electrode and the foamed cement isolation layer, and the second polymer gel layer is arranged between the second cement-based electrode and the foamed cement isolation layer; wherein the first polymer gel layer and the second polymer gel layer are each independently prepared by the following method: adding polymer powder to water and heating to dissolve, adding electrolyte (such as 1M potassium chloride solution) after cooling, and then adding a cross-linking agent to mix, pouring the mixed solution into a mold or a plate, and obtaining a polymer gel layer after drying.

[0033] Preferably, the polymer powder is one or more selected from polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyurethane (PU), polyimide (PI), polycarbonate (PC), preferably polyvinyl alcohol (PVA);

[0034] Preferably, the heating and dissolving temperature is 80-90°C;

[0035] Preferably, the electrolyte concentration is 1M, and the mass of the electrolyte accounts for 5-30% of the total mass of the gel;

[0036] Preferably, the crosslinking agent is one or more selected from boric acid, vinyl trifluoroethyl silane (VTES), amino silane (APTES), preferably boric acid; the amount of the crosslinking agent added is 1%-5% of the total mass of the polymer powder;

[0037] Preferably, the thickness of the first polymer gel layer and the second polymer gel layer are each independently 5-20 mm.

[0038] Before being assembled into a supercapacitor, the polymer gel is washed with distilled water to remove unreacted cross-linking agent and other impurities, and the gel is soaked in an electrolyte (such as 1M potassium chloride solution) for a period of time to ensure that the electrolyte is completely permeated into the gel.

[0039] By further using a highly water-absorbent polymer gel as a storage device for the electrolyte, the electrolyte inside the gel is released and replenished into the electrode, greatly improving the cycle performance of the capacitor.

[0040] In a second aspect, the present invention provides a method for preparing the above-mentioned all-cement-based supercapacitor, comprising the following steps:

[0041] The first cement-based electrode and the second cement-based electrode are prepared independently: conductive carbon black and cement are mixed to obtain a dry mixture, water and a water reducing agent are added, mixed and stirred to obtain a cement-based slurry; the cement-based slurry is poured into a mold and vibrated, and after hardening, the slurry is demoulded, cured, cut and polished to obtain a cement-based electrode;

[0042] Preparation of a foamed cement isolation layer: Cement and water are mixed and stirred evenly to form a cement slurry; H2O2 with a concentration of 2% to 4% is added to the cement slurry, poured into a mold, and demolded and cured after forming to obtain a foamed cement isolation layer;

[0043] The first cement-based electrode and the second cement-based electrode are immersed in an electrolyte until saturated, and the first cement-based electrode, the foamed cement isolation layer, and the second cement-based electrode are stacked in order to obtain a full cement-based supercapacitor.

[0044] In some embodiments, the preparation method further comprises:

[0045] The first foamed cement bearing layer and the second foamed cement bearing layer are prepared independently: cement, water and fine aggregate are mixed and stirred evenly to form cement slurry; H2O2 with a concentration of 6% to 10% is added to the cement slurry, poured into a mold, demolded and cured after forming, and the foamed cement bearing layer is obtained;

[0046] The first foamed cement bearing layer, the first cement-based electrode, the foamed cement isolation layer, the second cement-based electrode and the second foamed cement bearing layer are stacked and combined in order to obtain a full cement-based supercapacitor.

[0047] In some embodiments, the preparation method further comprises:

[0048] The first polymer gel layer and the second polymer gel layer are prepared independently: polymer powder is added into water and heated to dissolve, electrolyte is added after cooling, and then a cross-linking agent is added and mixed, the mixed solution is poured into a mold or a plate, and the polymer gel layer is obtained after drying;

[0049] The first polymer gel layer and the second polymer gel layer are immersed in an electrolyte until saturated, and the first foamed cement bearing layer, the first cement-based electrode, the first polymer gel layer, the foamed cement isolation layer, the second polymer gel layer, the second cement-based electrode and the second foamed cement bearing layer are stacked in this order to obtain a full cement-based supercapacitor.

[0050] The specific description of each step is the same as that of the first aspect and will not be repeated here.

[0051] Beneficial effects:

[0052] The present invention can significantly improve the service life of the capacitor by using porous foamed cement to replace the traditional fiber diaphragm; further, a foamed cement bearing layer and a highly absorbent polymer gel layer are used to protect the capacitor and greatly improve its physical properties; the electrolyte inside the polymer gel is released and replenished into the electrode, thereby realizing intermittent supply of capacitor electrolyte and greatly improving the cycle performance of the capacitor.

[0053] When using this capacitor system, the compression resistance of the foamed cement diaphragm is 2 times higher than that of the ordinary fiber diaphragm, and the cycle performance of the polymer gel layer is 2 times higher than that without adding the gel layer.

[0054] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 A schematic diagram of a supercapacitor of the present invention is shown;

[0056] Figure 2 Shown are cyclic voltammetry test diagrams of embodiments and comparative examples;

[0057] Figure 3 The changing trends of the cross-current charge and discharge times and the coulombic efficiency of Example 3 and Comparative Example 1 are shown.

[0058] Illustration: 1-first foamed cement bearing layer (second foamed cement bearing layer); 2-first cement-based electrode (second cement-based electrode); 3-first polymer gel layer (second polymer gel layer); 4-foamed cement isolation layer. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0060] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0061] Test method:

[0062] Compressive strength: Use MTS universal testing machine with fixture for testing, refer to GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0063] Electrical properties of supercapacitors:

[0064] The electrochemical measurements were all performed on a CHI760e electrochemical workstation (Chenhua, China) using a two-electrode system in the potential range of 0 to 1 V at a scan rate of 100 mV / s for cyclic voltammetry (CV) tests. The constant current charge / discharge (GCD) tests were performed at 10 mA / cm 2 carried out at a current density of .

[0065] Cycle number: Measured using the constant current charge and discharge method, the final number of cycles tested.

[0066] Coulomb efficiency: measured using the constant current charge and discharge method, Coulomb efficiency calculation formula Where E is the Coulomb efficiency, t discharge is the discharge time, t charge For charging time.

[0067] Specific capacitance: Use specific capacitance to define storage performance, use cyclic voltammetry in an electrochemical workstation, and calculate specific capacitance using the formula Where C is the specific capacitance, I is the test current, ΔV is the voltage gradient, u is the scan rate, U0 is the voltage window difference, and m is the mass of the active material (carbon black) used.

[0068] The materials and equipment used in the embodiments are as follows:

[0069] Ketchen Black was purchased from Xinghua Kaizheng New Energy Materials Co., Ltd., with a specific surface area of ​​1132m 2 / g;

[0070] Polycarboxylic acid high-efficiency water reducer was purchased from Qingdao Huatie Polycarboxylic acid High-Performance Water Reducer HT-300;

[0071] PVA powder was purchased from MacLean Reagent Co., Ltd.

[0072] Preparation Example 1 Preparation of cement-based electrode

[0073] Preparation of the first cement-based electrode: Take 250g of Ketjen black and 2000g of 425# Portland cement at a Ketjen black / cement mass ratio of 12.5%, stir the mixture for 20 minutes to obtain a dry mixture; at a water-cement ratio of 1.5, pour water and polycarboxylic acid high-efficiency water reducer (the mass of the water reducer is 2% of the mass of water) into the dry powder mixture and stir for 20 minutes, pour into a 20cm*20cm*30cm mold and place it on a vibrating table for 10 minutes; after hardening, demold and place in a curing box at a temperature of 20±2℃ and a relative humidity controlled at more than 95% for 28 days. Cut after curing, the sample thickness after cutting is 20mm, and single-sided polishing. Prepare the second cement-based electrode in the same way.

[0074] Preparation Example 2 Preparation of foamed cement bearing layer

[0075] Prepare the first foamed cement bearing layer: take about 3000g of cement and 6000g of sand (fineness modulus 2.8), and mix the cement with a water-cement ratio of 0.4 to form a uniform cement slurry, and about 0.5 liters of hydrogen peroxide (8% concentration solution); slowly add the hydrogen peroxide solution to the prepared cement slurry. Stir slowly at the edge to ensure that the hydrogen peroxide is evenly dispersed in the cement slurry; pour into a 20cm*20cm*5cm mold, wait for molding and demoulding, place in a standard curing room for 28 days, and prepare the first foamed cement bearing layer. Prepare the second foamed cement bearing layer in the same way.

[0076] Preparation Example 3 Preparation of foamed cement isolation layer

[0077] Preparation of foamed cement isolation layer: Similar to the steps of Preparation Example 2, except that no sand is added, the concentration of hydrogen peroxide is 3%, the mold thickness is 2 mm, and the remaining steps are the same.

[0078] Preparation Example 4 Preparation of polymer gel layer

[0079] Preparation of the first polymer gel layer: Add about 1000 ml of distilled water to a container of sufficient capacity, place the container in a hot water bath at 90°C, gradually add about 200 g of PVA powder, and continue stirring until the PVA is completely dissolved; add 360 g of 1M KCl electrolyte solution to the dissolved PVA solution, add 2% of the PVA mass of boric acid crosslinker to the solution, continue stirring, pour the mixed PVA solution into a 20cm*20cm*1cm mold, place it in a drying oven, slowly dry the gel at 25°C, and wash the gel with distilled water to remove unreacted crosslinker and other impurities. Prepare the second polymer gel layer in the same way.

[0080] Example 1

[0081] A full cement-based supercapacitor is obtained by immersing the prepared first cement-based electrode and the second cement-based electrode in 1M KOH until saturated, and stacking the first cement-based electrode, the foamed cement isolation layer, and the second cement-based electrode in order to obtain a supercapacitor.

[0082] Example 2

[0083] A full cement-based supercapacitor is obtained by immersing the prepared first cement-based electrode and the second cement-based electrode in 1M KOH until saturated, and stacking them in the order of a first foamed cement bearing layer, a first cement-based electrode, a foamed cement isolation layer, a second cement-based electrode, and a second foamed cement bearing layer to obtain a supercapacitor.

[0084] Example 3

[0085] A full cement-based supercapacitor, wherein the prepared first cement-based electrode and the second cement-based electrode, the first polymer gel layer and the second polymer gel layer are immersed in 1M KOH until saturated, and the supercapacitor is Figure 1 A supercapacitor is obtained by sequentially stacking a structure (a first foamed cement bearing layer, a first cement-based electrode, a first polymer gel layer, a foamed cement isolation layer, a second polymer gel layer, a second cement-based electrode, and a second foamed cement bearing layer).

[0086] Example 4

[0087] The preparation process is basically the same as that of Example 1, except that the thickness of the foamed cement isolation layer is 5 mm.

[0088] Example 5

[0089] The preparation process is basically the same as that of Example 1, except that the thickness of the foamed cement isolation layer is 10 mm.

[0090] Comparative Example 1

[0091] The preparation process is basically the same as that of Example 1, except that the foamed cement isolation layer is replaced by a glass fiber membrane.

[0092] The results of the embodiments and comparative examples are shown in the following table.

[0093] Test piece Cycle times Specific capacitance (F / g) Compressive strength(MPa) Example 1 3942 0.12 31.5 Example 2 4052 0.13 35.2 Example 3 >10000 0.21 35.7 Example 4 4079 0.09 37.6 Example 5 3990 0.07 39.1 Comparative Example 1 3320 0.15 15

[0094] Result analysis:

[0095] The use of cement diaphragms to replace traditional glass fiber diaphragms has greatly improved the physical properties of the unit capacitor. With the force-bearing layer, it is more suitable for practical engineering applications and is expected to be made into assembled capacitor components, connected in series or parallel to adapt to large-scale energy storage. In addition, the addition of a gel layer in Example 3 improves the cycle stability of this capacitor.

[0096] Figure 2 It can be seen that Figure 2 The cyclic voltammetry test of each embodiment and comparative example was performed at a scan rate of 100 nV / s. The CV curves of each specimen were full and shuttle-shaped, showing the superiority of the double electric layer. At a high scan rate, the CV curves still had considerable capacitance.

[0097] Figure 3 It can be seen that Figure 3 The variation trends of the cross-current charge and discharge times and the coulombic efficiency of Example 3 and Comparative Example 1 are shown. The addition of the gel layer greatly improves the cycle times and cycle stability.

[0098] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A fully cement-based supercapacitor, characterized in that: It includes a first cement-based electrode, a second cement-based electrode, and a foamed cement isolation layer between the first cement-based electrode and the second cement-based electrode; The foamed cement isolation layer is prepared by the following method: Cement and water are mixed and stirred evenly to form cement slurry; H2O2 with a concentration of 2% to 4% is added to the cement slurry, poured into a mold, and demolded and cured after forming to obtain a foamed cement isolation layer.

2. The all-cement-based supercapacitor according to claim 1, characterized in that: The cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement; The water-cement ratio is 0.3-0.6; The curing temperature is 20±2℃, the relative humidity is controlled above 95%, and the curing period is more than 28 days.

3. The all-cement-based supercapacitor according to claim 1, characterized in that: The thickness of the prepared foamed cement isolation layer is 1-10 mm; The pores of the prepared foamed cement isolation layer are 0.5-5 μm.

4. The all-cement-based supercapacitor according to claim 1, characterized in that: The first cement-based electrode and the second cement-based electrode are each independently prepared by the following method: Conductive carbon black and cement are mixed to obtain a dry mixture, water and a water reducing agent are added and mixed to obtain a cement-based slurry; the cement-based slurry is poured into a mold and vibrated, and after hardening, it is demolded, cured, cut, and polished to obtain a cement-based electrode.

5. The all-cement-based supercapacitor according to claim 4, characterized in that: The mass of conductive carbon black accounts for 8% to 13% of the mass of cement; The water reducer is one or more selected from polycarboxylic acid high-efficiency water reducer, naphthalene-based high-efficiency water reducer, and aminosulfonate-based high-efficiency water reducer; The water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 2% to 4% of the mass of water; The thickness of the first cement-based electrode and the second cement-based electrode are each independently 1-30 mm.

6. The all-cement-based supercapacitor according to claim 1, characterized in that: The all-cement-based supercapacitor also includes: a first foamed cement bearing layer and a second foamed cement bearing layer, wherein the first foamed cement bearing layer is arranged on the side of the first cement-based electrode away from the foamed cement isolation layer, and the second foamed cement bearing layer is arranged on the side of the second cement-based electrode away from the foamed cement isolation layer; wherein the first foamed cement bearing layer and the second foamed cement bearing layer are independently prepared by the following method: mixing cement, water and fine aggregate, stirring evenly to form cement slurry; adding H2O2 with a concentration of 6% to 10% to the cement slurry, pouring it into a mold, demolding and curing after forming, and obtaining a foamed cement bearing layer; Preferably, the thickness of the first foamed cement bearing layer and the second foamed cement bearing layer are independently 10-50 mm; The pores of the first foamed cement bearing layer and the second foamed cement bearing layer are independently 0.2-1 mm.

7. The all-cement-based supercapacitor according to claim 6, characterized in that: The all-cement-based supercapacitor also includes: a first polymer gel layer and a second polymer gel layer, wherein the first polymer gel layer is arranged between the first cement-based electrode and the foamed cement isolation layer, and the second polymer gel layer is arranged between the second cement-based electrode and the foamed cement isolation layer; wherein the first polymer gel layer and the second polymer gel layer are independently prepared by the following method: adding polymer powder to water, heating and dissolving, adding electrolyte after cooling, and then adding a cross-linking agent to mix, pouring the mixed solution into a mold or a plate, and obtaining the polymer gel layer after drying; Preferably, the polymer powder is one or more selected from polyvinyl alcohol, polytetrafluoroethylene, polyurethane, polyimide, and polycarbonate; the crosslinking agent is one or more selected from boric acid, vinyl trifluoroethylsilane, and aminosilane; and the amount of the crosslinking agent added is 1%-5% of the total mass of the polymer powder; Preferably, the thickness of the first polymer gel layer and the second polymer gel layer are each independently 5-20 mm.

8. A method for preparing a fully cement-based supercapacitor according to any one of claims 1 to 7, characterized in that: The steps include: The first cement-based electrode and the second cement-based electrode are prepared independently: conductive carbon black and cement are mixed to obtain a dry mixture, water and a water reducing agent are added, mixed and stirred to obtain a cement-based slurry; the cement-based slurry is poured into a mold and vibrated, and after hardening, the slurry is demoulded, cured, cut and polished to obtain a cement-based electrode; Preparation of a foamed cement isolation layer: Cement and water are mixed and stirred evenly to form a cement slurry; H2O2 with a concentration of 2% to 4% is added to the cement slurry, poured into a mold, and demolded and cured after forming to obtain a foamed cement isolation layer; The first cement-based electrode and the second cement-based electrode are immersed in an electrolyte until saturated, and the first cement-based electrode, the foamed cement isolation layer, and the second cement-based electrode are stacked in order to obtain a full cement-based supercapacitor.

9. The preparation method according to claim 8, characterized in that: The preparation method further comprises: The first foamed cement bearing layer and the second foamed cement bearing layer are prepared independently: cement, water and fine aggregate are mixed and stirred evenly to form cement slurry; H2O2 with a concentration of 6% to 10% is added to the cement slurry, poured into a mold, demolded and cured after forming, and the foamed cement bearing layer is obtained; The first foamed cement bearing layer, the first cement-based electrode, the foamed cement isolation layer, the second cement-based electrode and the second foamed cement bearing layer are stacked and combined in order to obtain a full cement-based supercapacitor.

10. The preparation method according to claim 9, characterized in that: The preparation method further comprises: The first polymer gel layer and the second polymer gel layer are prepared independently: polymer powder is added into water and heated to dissolve, electrolyte is added after cooling, and then a cross-linking agent is added and mixed, the mixed solution is poured into a mold or a plate, and the polymer gel layer is obtained after drying; The first polymer gel layer and the second polymer gel layer are immersed in an electrolyte until saturated, and the first foamed cement bearing layer, the first cement-based electrode, the first polymer gel layer, the foamed cement isolation layer, the second polymer gel layer, the second cement-based electrode and the second foamed cement bearing layer are stacked in this order to obtain a full cement-based supercapacitor.

Citation Information

Cited By

  • Cement-based electrode, capacitor and preparation method thereof

    CN121237574A

  • Cement-based electrode, capacitor and method for manufacturing the same

    CN121237574B

  • A magnesium phosphate cement supercapacitor with gradient interpenetrating interface and a preparation method thereof

    CN122619600A